PENGARUH WORK OVERLOAD DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DI BADAN PUSAT STATISTIK KABUPATEN BULELENG - Wirani, Putu; Sari Sanjaya, Ni Made Wulan (Komunitas Manajemen Kompetitif, 2024)
Human resources play a very important role in realizing the vision,mission, and as well as the role, the performance of human resourcescontributes to the success and sustainability of an organization. Qualityhuman resources can certainly help achieve the goals of any organizationor agency. The purpose of this study is to determine the Effect of Work Overload and Work Environment on EmployeePerformance at the Central Bureau of Statistics of Buleleng Regency.Thestudy uses quantitative methods using data from the results of questionnairedistribution. The sample in this study was 33 employees of BPS BulelengRegency.Data analysis technique using multiple linear regression. Theresults of this study show that: (1) Work overload affects employeeperformance. (2) Work Environment does not affect employee performance.(3) Simultaneously Work overload and work environment affect employeeperformance at the Central Bureau of Statistics of Buleleng district.